Criminal Law Reform Through the Classification: Toward a Restorative Sanctions in Indonesian Immigration Law (Lex Scientia Law Review, 2025)
The enactment of the National Criminal Code in 2023 marks a significant shift in Indonesia's sentencing policy by promoting the ultimum remedium principle and prioritizing fines as the main form of punishment. These reforms aim to address the long-standing problem of prison overcapacity caused by the overuse of prison sentences and to promote restorative justice. The National Penal Code introduces a structured classification of fines, providing clear categories to reduce sentencing disparities and anticipate economic fluctuations. This classification is intended to serve as a reference for specific legislation, including the Immigration Act, where the main criminal sanction consists of imprisonment with fines as an alternative or cumulative punishment. This normative juridical research examines the integration of the National Criminal Code fine classification into the immigration law enforcement framework in Indonesia. The findings of this study reveal that although administrative measures such as deportation are more often imposed in practice, the lack of deterrent effect is still a concern. Integrating fine classification into immigration administrative measures offers a balanced solution by combining procedural efficiency with the deterrent effect. This research recommends harmonizing administrative fines with the classification system in the National Criminal Code to enhance fairness, legal certainty, and deterrence of violations in immigration law enforcement while ensuring the protection of individual rights.